قادیانیت کے محرکات ومضمرات: تجزیاتی مطالعہ (Al-Qamar, 2019)
The finality of the prophet hood of Muhammad (PBUH) has been the cornerstone of the Muslim faith since almost fourteen hundred years. A number of self-styled prophets have claimed themselves to be the messengers of God but the mainstream of Muslims has always disavowed the veracity of their claims in line with the injunctions and the generally accepted interpretation of Islam. Deviating from the mainstream interpretation, a religion spearheaded by Mirza Ghulam Ahmad has claimed to be a new version of Islam since 19th century. His claim to the prophet hood has been countered by Islamic scholars since his emergence. In the following lines, an attempt will be made to analyze the motives and implications that underlie the framework of the so called version led by Mirza Ghulam Muhammad Qadiyani in an attempt to expose the inherent caveats in this new religion.
Keywords: Qadianiyat; motives; implications